Tourism Stocks in Times of Crisis: An Econometric Investigation of Unexpected Nonmacroeconomic Factors. (March 2019) - Zopiatis, Anastasios; Savva, Christos S.; Lambertides, Neophytos; McAleer, Michael
The relationship between the tourism industry and unexpected nonmacro incidents has received limited academic coverage. As a result, the quantifiable impact of such events on tourism-specific stock values, both in terms of returns and volatility, remains grossly underexamined. Motivated by the reasoning that the well-established features inherent to the tourism industry may trigger a different pattern of stock price movement compared with other industries, and by using econometric methodology, this article investigates the reaction of five hospitality/tourism stock indices to 150 incidents, depicting major Acts of Terrorism, natural catastrophes, and War conflicts that have taken place since the year 2000. Empirical findings underscore the effect of such incidents on stock indices, with distinctive differences among the types and specificities of each event under investigation. This article contributes to the extant literature and enhances our conceptual capital pertaining to the tourism industry's current financial practices related to stock performance and behavior.